Adult learning and vocational training in post- covid-19 era: Issues, challenges and prospects - Okunna, O. K.; Iwundu, S. P.; Chukwuemerie, O. C. (Journal of Research in Adult and Continuing Education, 2023)
This paper examined the issues, challenges, and prospects of adult learning and vocational training in the post–COVID 19 era. The impact of the pandemic on adult learning and vocational training is discussed in details, based on issues identified from an extensive review of relevant literatures. Some of the issues identified include increased level of isolation, a shift in the way lifelong learning is provided, and a new level of digital literacy required for adult learners to access training opportunities. Furthermore, challenges such as difficulties in providing access to resources and in addressing the loss of jobs, as well as a lack of policy infrastructure to support adult learning and vocational training, are discussed. Strategies to provide equitable access to opportunities are suggested and the prospects of virtual learning and online education are explored. The paper concludes with some thoughts on the potentials of adult learning and vocational training in the post-COVID 19 environment.
Keywords: Adult Learning; Vocational Training; Post-COVID- 19